أثر استخدام منظمات التفكير البصري في تنمية التحصيل ومهارات العمل ضمن الفريق لدى طالبات مقرر طرق تدريس الرياضيات بجامعة أم القرى - البركاتي، نيفين بنت حمزة بن شرف (جامعة القصيم, 2019)
هدفت الدراسة الحالية إلى بحث أثر استخدام منظمات التفكير البصري في تنمية التحصيل ومهارات العمل ضمن الفريق لدى طالبات الرياضيات في مقرر طرق تدريس الرياضيات بمرحلة الإعداد التربوي بجامعة أم القرى، وقد قامت الباحثة بصياغة ثلاث فرضيات في سبيل الإجابة على أسئلة الدراسة، حيث استخدمت المنهج التجريبي والتصميم شبه التجريبي ذي المجموعتين التجريبية والضابطة، وتم بناء اختبار تحصيلي، ومقياس لمهارات العمل ضمن الفريق، وطبقت الدراسة على عينة عشوائية بلغ عدد أفردها (84) طالبة من طالبات الإعداد التربوي بجامعة أم القرى تخصص رياضيات (٤٢) طالبة للمجموعة التجريبية، و(٤٢) طالبة للمجموعة الضابطة، وتم استخدام اختبار (ت) للمجموعات المستقلة كأسلوب إحصائي لتحليل بيانات الدراسة، وتوصلت الدراسة إلى النتائج التالية: توجد فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسط درجات طالبات المجموعة التجريبية التي تدرس باستخدام منظمات التفكير البصري والمجموعة الضابطة التي تدرس باستخدام الإلقاء في التطبيق البعدي للاختبار التحصيلي لصالح المجموعة التجريبية ذات المتوسط الأكبر في التحصيل، وتوجد فروق ذات دلالة إحصائية عند مستوى (0.05) بين متوسطي درجات طالبات المجموعة التجريبية التي تدرس باستخدام منظمات التفكير البصري والمجموعة الضابطة التي تدرس باستخدام الإلقاء في التطبيق البعدي لمقياس مهارات العمل ضمن الفريق لصالح المجموعة التجريبية ذات المتوسط الأكبر في مهارات العمل الجماعي لكل مهارة على حدة ولمهارات العمل الجماعي مجتمعة، وتوجد علاقة ارتباطية ذات دلالة إحصائية عند مستوى (0.05) بين متوسطي درجات طالبات المجموعة التجريبية في التطبيق البعدي بين التحصيل ومهارات العمل بالفريق متوسطة طردية بين التحصيل ومهارات العمل الجماعي أي كلما زادت مهارات العمل زاد التحصيل.
The aim of this study is to investigate the effect of using visual thinking organizers in enhancing the achievement and group work skills in female students enrolled in a course: MTMC methods of teaching mathematics course, at the level of educational diploma in Um Al-Qura University. The researcher used the experimental and quasi- experimental methods of two groups: control group and experimental group. An achievement test has been used, as well as a scale of working in a group. The sample (n=84) were randomly chosen and were divided into two equal groups. T-test was applied. The findings were as follow: Significant differences (0.05) between means of achievement in the post test of the two groups, for the benefit of the experimental group who studied by visual thinking organizers, not the control group who studied traditionally. Significant differences (0.05) between means of group work skills scale in the post test of the two groups, for the benefit of the experimental group who studied by visual thinking organizers, not the control group who studied traditionally. (Each skill of the group work skills in the scale, and the sub total of the scale) Significant positive correlation (0.05) between the two means in both posttests: the achievement and the scale of group working skills. This study came up with some recommendations: Using strategy of visual thinking organizers in general, and in mathematic courses specifically. Get university students a training course focus on the skills of visual thinking organizers. Develop new strategies, manuals, and cards to enhance the skills of working in a group. Get group working more affective in Mathematic classes because it increases the cooperation between the community members. Get the university students training courses on a subject of group working skills in all activities and classes.
Keywords: التفكير البصري -- التحصل الدراسي -- مادة الرياضيات -- الجامعات السعودية